Comparative Study of the Efficiency of the Inactivated H9n2 Vaccine against Avian Influenza in Broiler Chickens - Assia Allaoui, Karina Bachtarzi, Lilia Belkacem, Mohamedsalah Beguiret, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Our work is devoted to a serological study of avian influenza disease in broiler chickens, after five different vaccine protocols. Methods: a total of 500 broiler chicks (day-old) were equitably divided into 5 lots. in each batch a specific vaccination protocol was followed. The relative level of serum antibodies against H9N2 virus present in the samples is determined at days: 1, 10, 24, 33, and 51 of age. Results: for batches 1 and 2: the kinetics of the antibodies present a stable curve not associated with significant modifications (p> 0.05) during the entire experimental period, whereas for batches 3, 4 and 5: a peak is observed at D 33 for the first two batches and at D51 for the last Conclusion: the development of active immunity conferred by vaccinations has not been proven because in groups 3, 4 and 5 the titers of antibodies reach high values ​​only in the case of response to the provoked infectious condition and not following immunization by vaccines. Keywords: antibodies, ELISA method, immunity, serotype H9N2, vaccine.